2010
DOI: 10.2223/jped.2025
|View full text |Cite
|
Sign up to set email alerts
|

Misreporting of dietary energy intake in adolescents

Abstract: Objectives: To examine the prevalence of under and overreporting of energy intake in adolescents and their associated factors. Methods:Cross-sectional study with 96 postpubertal adolescents (47 normal-weight and 49 obese), mean age of 16.6±1.3 years. Weight and height were measured, and body mass index was calculated. Body composition was assessed by dual energy X-ray absorptiometry. Dietary intake was evaluated by a 3-day dietary record. Biochemical assessment was performed (serum total cholesterol, LDL-chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Although the included studies show an important methodological heterogeneity regarding the content of their interventions, their durations and the assessment of body composition or other physical characteristics, they all used dietary recall to assess food intake. Yet this remains a self‐reported method to assess energy consumption that is highly subjective (especially among children and adolescents with obesity) , and its use in all the selected studies facilitates comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Although the included studies show an important methodological heterogeneity regarding the content of their interventions, their durations and the assessment of body composition or other physical characteristics, they all used dietary recall to assess food intake. Yet this remains a self‐reported method to assess energy consumption that is highly subjective (especially among children and adolescents with obesity) , and its use in all the selected studies facilitates comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main pitfalls in dietary assessment by self-reported dietary recall is underreporting energy intake in youth overweight participants [37,38]. To account for this, we conducted sensitivity analyses and excluded under-reporters from the analyses and the results did not change.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a majority of self-reported energy intake data from the National Health and Nutrition Examination Survey (NHANES) are not physiologically plausible (Archer, Hand, & Blair, 2013). Moreover, there are examples of both under-and over-reporting across other studies that use self-reported energy intake, particularly in children and adolescents (Fisher, Johnson, Lindquist, Birch, & Goran, 2000;Forrestal, 2011;Santos, Pascoal, Fisberg, Cintra, & Martini, 2010). Heavier youth are more likely to underreport the amount they eat on self-report measures compared to their actual intake (Wolkoff et al, 2011).…”
Section: Introductionmentioning
confidence: 99%